2016
DOI: 10.2147/ott.s88726
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-rich carcinoma of the breast that is strongly positive for estrogen receptor: a case report and literature review

Abstract: Lipid-rich carcinoma (LRC) of the breast is a rare breast cancer variant that accounts for <1% of all breast malignancies. It has been reported that LRCs are negative for estrogen receptor. Here, we report a case of LRC of the breast that was strongly positive for estrogen receptor and treated with endocrine adjuvant therapy. A 52-year-old postmenopausal female noticed a lump in her right breast by self-examination and presented to our hospital. Physical examination revealed an elastic 30 mm ×20 mm hard mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…This may probably confer an energetic advantage and favor the development of a more aggressive phenotype [ 108 ]. Also, breast lipid-rich carcinomas are usually, but not always [ 109 ], negative for the expression of estrogen receptors [ 110 ], thus implying more complex levels of regulation/stimulation of lipid synthesis and storage.…”
Section: Lipid Droplets and Cancermentioning
confidence: 99%
“…This may probably confer an energetic advantage and favor the development of a more aggressive phenotype [ 108 ]. Also, breast lipid-rich carcinomas are usually, but not always [ 109 ], negative for the expression of estrogen receptors [ 110 ], thus implying more complex levels of regulation/stimulation of lipid synthesis and storage.…”
Section: Lipid Droplets and Cancermentioning
confidence: 99%
“…The analysis of tumors from a computational approach showed that despite the heterogeneity of cancer cells, the majority displays an increased TAG content which might be attributable, at least partially, to the activation of lipogenic enzymes [144]. In fact, several cancer cells increase the uptake and storage of lipids in LDs via the overexpression of DGAT‐1 [140], SOAT‐1 [145] and SCD‐1 [146]. Moreover, an accumulation of CE was reported in pancreatic cancer patients and cell lines, where SOAT‐1 expression correlated with poor patient survival.…”
Section: Lipogenic Enzymes In Cancermentioning
confidence: 99%
“…Blocking SCD‐1 decreased LDs content and impaired cancer stemness and tumor initiation capacity by inactivating the NF‐κB (nuclear factor kappa B) pathway [135]. SCD‐1 upregulation also contributes to LD formation in response to hormones, such as progestin, in breast cancer [146]. Furthermore, LD accumulation enhances the metastatic potential of cancer cells through the upregulation of FASN expression, which stimulate prostaglandin E2 (PGE2) synthesis [122] and energy production [134], and DGAT‐2 which, in a C/EBPα‐dependent manner, triggers FAO and resistance to anoikis [131].…”
Section: Lipogenic Enzymes In Cancermentioning
confidence: 99%
“…The production of LDs is also observed in some breast cancers and is, associated with the presence of hormone receptors in cancer cells. This production appears to be induced during hormone-based treatment (e.g., progestin) [ 82 ]. However, triple-negative breast cancer cells may also exhibit LDs production associated with increased proliferation and motility.…”
Section: Lipid Droplets and Cancersmentioning
confidence: 99%